The Impact of Parental Divorce on Children's Psychology - Ramadani, Sufi; Fitriani, Wahidah; Yeni, Putri (Darussalam: Journal of Psychology and Educational, 2022)
Divorce is a condition where a wife is separated from her husband and vice versa, the husband leaves his wife which causes the loss of certain rights and obligations. Divorce that occurs of course has an impact and the main victims of divorce are the children in the family. This article aims to find out what impact children feel after their parents' divorce. The method used in this research is the library reaseach method (library study). Divorce that occurs has a positive and negative impact on children. However, from several studies that have been carried out, the negative impact is more dominant in children than the positive impact. To overcome psychological problems in children, help from the family and understanding of divorce is needed in society so as not to judge children.